2021
DOI: 10.51551/verimlilik.701270
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Investor Attention on Stock Return Volatility: An Econometric Application on Banks

Abstract: Trendleri) verileri kullanılarak ölçülen yatırımcı ilgisi ile pay senedi volatilitesi arasındaki ilişkinin araştırılması amaçlanmıştır. Yöntem: Çalışmada GAT verileri üzerinden ölçülen yatırımcı ilgisi ile koşullu varyans modelleri kullanılarak hesaplanan volatilite arasındaki ilişki, panel regresyon analizi ile incelenmiştir. Çalışmanın bağımlı değişkeni olan volatilite esas alınarak değişken bazında ve toplam GAT bazında olmak üzere iki model kurulmuştur. Bulgular: Yapılan analiz sonucunda, "banka adı hisse"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Therefore, series with stationary characteristics If the H 0 hypothesis is rejected, it is concluded that the Y variable is stationary, and if the H 0 hypothesis cannot be rejected, the Y variable is not stationary. At this point, the difference is taken until stationarity is achieved (Nur & Ege, 2019).…”
mentioning
confidence: 99%
“…Therefore, series with stationary characteristics If the H 0 hypothesis is rejected, it is concluded that the Y variable is stationary, and if the H 0 hypothesis cannot be rejected, the Y variable is not stationary. At this point, the difference is taken until stationarity is achieved (Nur & Ege, 2019).…”
mentioning
confidence: 99%